2017
DOI: 10.1128/aac.00469-17
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity and Cell Selectivity of Synthetic and Biosynthetic Cationic Polymers

Abstract: The mammalian and microbial cell selectivity of synthetic and biosynthetic cationic polymers has been investigated. Among the polymers with peptide backbones, polymers containing amino side chains display greater antimicrobial activity than those with guanidine side chains, whereas ethylenimines display superior activity over allylamines. The biosynthetic polymer ε-polylysine (εPL) is noncytotoxic to primary human dermal fibroblasts at concentrations of up to 2,000 μg/ml, suggesting that the presence of an iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 37 publications
2
64
0
Order By: Relevance
“…26,44,58 At 48 h post-inoculation the mean corneal thickness continued to increase for the control group (194.4 ± 27.4 μm) which indicates increased severity of the infection. 59 An even more intense reduction in the average corneal thickness was seen in the 0.15% pre-loaded L12 nanogel (112.7 ± 29.6 μm), 0.3% preloaded L12 nanogel (117.2 ± 8.7 μm) and 0.3% gatifloxacin (124.3 ± 18.7 μm) treated groups after 48 h.…”
Section: In Vivo Testing Of the L12 Nanogels In A Corneal Infection Wmentioning
confidence: 88%
“…26,44,58 At 48 h post-inoculation the mean corneal thickness continued to increase for the control group (194.4 ± 27.4 μm) which indicates increased severity of the infection. 59 An even more intense reduction in the average corneal thickness was seen in the 0.15% pre-loaded L12 nanogel (112.7 ± 29.6 μm), 0.3% preloaded L12 nanogel (117.2 ± 8.7 μm) and 0.3% gatifloxacin (124.3 ± 18.7 μm) treated groups after 48 h.…”
Section: In Vivo Testing Of the L12 Nanogels In A Corneal Infection Wmentioning
confidence: 88%
“…The polymer design and the polymer-membrane interactions are crucial issues for bacterial infection eradication. In a recent study, linear and branched PEI polymers were found to have very similar MIC values, while ε-polycaprolactone showed superior broad-spectrum antimicrobial properties over L-PEI [ 46 ]. Hence, in future work we will consider the use of a coarse-grain (CG) molecular dynamics model of L-OEI-h to better understand its interactions with bacterial and mammalian membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Membrane depolarization was monitored by using the cell membrane potential sensitive probe DiSC 3 -5 (Sigma, USA) [ 77 , 78 ]. Briefly, the bacterial cells were washed and diluted with 4-(2-hydroxyerhyl) piperazine-1-erhanesulfonic acid (HEPES), buffer (5 mM HEPES, 20 mM glucose, 100 mM potassium chloride, pH 7.4) to achieve a concentration of OD 630 = 0.05, and prepared in a 96-well polypropylene microtiter plate.…”
Section: Methodsmentioning
confidence: 99%